2017
DOI: 10.1038/cddis.2017.487
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motion regulates the activity of the Mitochondrial Serine Protease HtrA2

Abstract: HtrA2 (high-temperature requirement 2) is a human mitochondrial protease that has a role in apoptosis and Parkinson’s disease. The structure of HtrA2 with an intact catalytic triad was determined, revealing a conformational change in the active site loops, involving mainly the regulatory LD loop, which resulted in burial of the catalytic serine relative to the previously reported structure of the proteolytically inactive mutant. Mutations in the loops surrounding the active site that significantly restricted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 59 publications
0
38
0
Order By: Relevance
“…Here, it facilitates cell death through cleavage of apoptosis inhibitor proteins. 11 Its conformational plasticity is high; at least five different conformations of the enzyme are possible and necessary for proper activity. If a mutation leads to the destabilization of one conformation, the enzyme activity decreases significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it facilitates cell death through cleavage of apoptosis inhibitor proteins. 11 Its conformational plasticity is high; at least five different conformations of the enzyme are possible and necessary for proper activity. If a mutation leads to the destabilization of one conformation, the enzyme activity decreases significantly.…”
Section: Discussionmentioning
confidence: 99%
“…If a mutation leads to the destabilization of one conformation, the enzyme activity decreases significantly. 11 The exact mitochondrial function of the HTRA2 is not fully clear yet, but according to data from HTRA2 mutant mouse cells and cancer cell experiments, HTRA2 is essential for proper mitochondrial Ca 2þ sequestering and morphology. 12 One theory suggests that due to the similarity of HTRA2 to the bacterial chaperon DegP, HTRA2 presumably works as a chaperon in the mitochondrial intermembrane space.…”
Section: Discussionmentioning
confidence: 99%
“…Higher-order structures have been similarly reported in a human HtrA protease, HtrA1 (36); however, very little is known about them or what the physiological implications of oligomerization might be in this case. Biochemical studies of purified HtrA2 proteins have revealed that the canonical form of HtrA2 is a trimeric state, and, to the best of our knowledge, all crystal structures solved to date show the canonical trimer configuration (37)(38)(39). Possible oligomeric pathways for HtrA2 and their potential roles in mediating substrate binding and proteolytic activity remain unknown.…”
Section: Significancementioning
confidence: 99%
“…34 In the cases of HtrA2 and SpoIVB, the integral PDZ domain blocked the accessibility of the active site. [35][36][37] Thus, targeting the non-catalytic domains of serine proteases could also be a potential strategy for protease inhibition. In this mini-review, we focus on targeting the autolysis loop in the catalytic domain to regulate the catalytic activity of serine proteases.…”
Section: Introductionmentioning
confidence: 99%